Lombalgia na gestação - Carvalho, Maria Emília Coelho Costa; Lima, Luciana Cavalcanti [UNESP]; de Lira Terceiro, Cristovam Alves; Pinto, Deyvid Ravy Lacerda; Silva, Marcelo Neves; Cozer, Gustavo Araújo; Couceiro, Tania Cursino de Menezes (Elsevier, 2017)
Objective Low back pain is a common complaint among pregnant women. It is estimated that about 50% of pregnant women complain of some form of back pain at some point in pregnancy or during the postpartum period. The aim of this study was to evaluate the frequency of low back pain during pregnancy and its characteristics. Methods Cross‐sectional study with low‐risk pregnant women. After approval by the Human Research Ethics Committee and receiving written informed consent, we included pregnant women over 18 years of age and excluded those with psychiatric disorders, previous lumbar pathologies, and receiving treatment for low back pain. Results We interviewed 97 pregnant women. The frequency of low back pain was 68%. The mean age was 26.2 years and the median gestational age was 30 weeks. Fifty‐eight pregnant women declared themselves as brown (58%). Most (88.6%) were married or living in common‐law marriage, fifty‐six (57.7%) worked outside the home, and 71 (73.2%) had completed high school. Low back pain was more frequent during the second trimester of pregnancy (43.9%), referred to as a “burning” sensation in 37.8% of patients, with intermittent frequency in 96.9% of the women. The symptoms got worse at night (71.2%). Resting reduced low back pain in 43.9% of pregnant women, while the standing position for a long time worsened it in 27.2% of patients. Conclusion Low back pain is common in pregnant women, has specific characteristics, and is more frequent in the second trimester of pregnancy. This indicates the need for prevention strategies that enable better quality of life for pregnant women.
Low back pain during pregnancy
Keywords: Frequency and characteristics of low back pain; Low back pain; Pregnant women